2017
DOI: 10.1007/s13280-016-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate change stimulates the growth of the intertidal macroalgae Ascophyllum nodosum near the northern distribution limit

Abstract: Ascophyllum nodosum is a foundation macroalgae of the intertidal zone that distributes across latitude 41.3–69.7°N. We tested the hypothesis that growth of A. nodosum near the northern distribution edge increases with warming. We retrospectively quantified the growth of eight A. nodosum populations at West Greenland and North Norway (from 64°N to 69°N). For seven populations, we measured growth rates since 1997–2002 and for one of them we extended the time series back to 1956 using published estimates. Individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 42 publications
(63 reference statements)
0
45
0
Order By: Relevance
“…Arctic warming therefore negatively affects the abundance of some Arctic species, while potentially benefiting temperate species (e.g. through increased growth, abundance and biodiversity) as poleward geographical ranges expand and new habitats become available (Wȩ sławski et al 2010, Poloczanska et al 2016, Marbà et al 2017. Thus, the potential positive effects on temperate species at their poleward distribution edge need to be studied further.…”
Section: Introductionmentioning
confidence: 99%
“…Arctic warming therefore negatively affects the abundance of some Arctic species, while potentially benefiting temperate species (e.g. through increased growth, abundance and biodiversity) as poleward geographical ranges expand and new habitats become available (Wȩ sławski et al 2010, Poloczanska et al 2016, Marbà et al 2017. Thus, the potential positive effects on temperate species at their poleward distribution edge need to be studied further.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing summer SST is the primary driver of shifts of the southern (warm) range limit, as SST surpasses growth and mortality thresholds. Whereas, increasing winter SST facilitates faster growth rates (Bolton & Lüning, ; Marbà et al, ) and greater recruitment (Filbee‐Dexter et al, ). Diffuse attenuation and sea ice coverage were also important predictors for seaweed distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, projected SST increases, decreases in ice cover, and changing salinity and turbidity patterns in the Arctic will generally have positive effects on the distributional range and production of fucoids and kelps (Filbee‐Dexter et al, ; Marbà et al, ). Yet the projected northward spread of temperate/boreal species may negatively affect established species such as F. evanescens (Küpper et al, ) and the endemic kelp L. solidungula (Filbee‐Dexter et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features can also be used to evaluate seawater quality and water pollution. For example, studying the growth and productivity of the macroalgae Ascophyllum nodosum , is suited to monitor the global warming effects at West Greenland and North Norway . In a different study, it was found that another brown alga, Padina pavonica , can be used as bioindicator to assess ocean acidification since P. pavonica is a sensitive reporter of acute environmental pH changes; acidified conditions induce decalcification and the uncovered P. pavonica is subject to the dangers posed by exposure to high light …”
Section: Incidence Of Algae In Response To Climate Changementioning
confidence: 99%